Natural disasters on the village district of Villa Restrepo, Ibagué (Colombia) - Néstor Andrés Guarnizo Sánchez; Fernando Andrés Estévez Suárez; Ruby Milena Bermúdez López (ARQUISUR Revista)
Population growth and urban expansion have led to excessive land exploitation, exhausting fundamental resources such as water and forests, which brought about various environmental hazards in several territories. This article addresses a qualitative approach to analyze the irretrievable damage that proliferation of settlements on the village of Villa Restrepo in the city of Ibagué has caused in the surrounding natural environment, mainly in the areas nearby Combeima river. Having performed a random probabilistic selection of inhabitants, the study delves into the community’s perceptions of the environmental impacts they face, such as biodiversity loss, land degradation, and Combeima river deterioration. Excessive and unplanned urbanization has increased risks associated with both natural phenomena and anthropic factors related to inadequate land management as regards territorial planning.